- Diagnostic value of CRP, PCT, NC and NLR in peripheral blood for bacterial infections in Non-small cell lung cancer patients after chemotherapy: CRP, PCT, NC and NLR in peripheral blood - Wang, Bin; Wei, Yanbin (Journal of Medical Biochemistry, 2025)
Objective: We attempted to clarify and compare diagnostic value of CRP, PCT, NC and NLR in peripheral blood for bacterial infections of non-small cell lung cancer (NSCLC) patients after chemotherapy.Methods: The 122 NSCLC patients under treatment in our hospital from October 2021 to October 2024 received selection as research cohort; among them, 50 NSCLC patients with bacterial infections after chemotherapy received selection as infection group and 50 NSCLC patients without bacterial infection after chemotherapy received selection as non-infection group. The general data, overall survival as well as CRP, PCT, NC and NLR levels in both groups received comparison.Results: The CRP, PCT, NC and NLR levels in infection group demonstrated elevation in comparison to those in non-infection group (P < 0.05). The overall survival demonstrated no difference in infection group in comparison to that in non-infection group (P = 0.749). The AUC values of CRP, PCT, NC and NLR for diagnosing bacterial infections in NSCLC patients after chemotherapy received comparison, illustrating statistical significance (P < 0.05); among them, PCT had the highest AUC value of 1.000, and next was AUC value of NLR (0.981).Conclusion: Application value of novel indicators such as PCT and NLR in diagnosing bacterial infections in advanced NSCLC patients after chemotherapy should be paid more attention to. The combination of the two may elevate efficacy of early diagnosis of bacterial infections.
Keywords: Non-small cell lung cancer; bacterial infections; CRP; PCT; NC; NLR